Pengaruh Efisiensi Biaya Produksi, Kegagalan Eksternal dan Kegagalan Internal Terhadap Volume Penjualan pada PT. Prima Alloy Steel di Sidoarjo - -, Sjafii - (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
Many valuable choices of goods and services are offered cause consummers or society more selective to choose or buy goods and services they need, both the quality of products are offered and sold in the market. Beside that, the distribution of selling must be common attention for producers because it is a mediumm for producers to distribute their products to consummers. Base on that background, the purpose of this experiment is to analyze the efficency influency of production expense, external failures and internal failures and selling volume which obtained from PT. Prima Alloy Steel in Sidoarjo. It uses 36 samples are observed since period 2004 - 2006. To the result which appropriate the experiment purposes. Itâs tried by multiples regression linear. The experiment result shows that the efficiency of production expence, internal failures and external failures influence tha volume of selling obviously, and the efficiency of production expense is more dominant variabel than gives influence to the selling volume. Keywords: The efficiency of production expense, external failures, internal failures, selling volume.